Comorbidity between personality disorders and depressive symptomatology in women: A cross‐sectional study of three different transitional life stages. (25th March 2013) - Enfoux, Aurore; Courtois, Robert; Duijsens, Inge; Reveillere, Christian; Senon, Jean Louis; Magnin, Guillaume; Voyer, Melanie; Montmasson, Helene; Camus, Vincent; El‐Hage, Wissam
ABSTRACT This study assessed the prevalence of personality disorders (PDs), according to DSM‐IV criteria, in relation to depressive symptomatology at three different periods of life in female subjects. Depressive symptoms and personality disorders were assessed in a sample of 568 women from three different transitional stages: 134 students, 314 primiparous women after childbirth and 120 women diagnosed with breast cancer. Depressive symptoms were assessed by the Hospital Depression and Anxiety Scale in the first and third groups and by the Edinburgh Post‐natal Depression Scale in the second group, whereas PDs were assessed by the French version of the Vragenlijst voor Kenmerken van de Persoonlijkheid. Depressive symptomatology and rates of PD (20.4% and 6.3%) were equivalent in the three groups. The prevalence of PD was higher in the depressed group compared with the non‐depressed group, with more paranoid, borderline, avoidant, obsessive–compulsive, schizotypal, antisocial, dependent and histrionic PD. Our findings support the hypothesis that PDs are more frequently associated with depressive symptoms. Borderline and avoidant PDs were more prevalent among young women. All cluster C PD (dependent, avoidant and obsessive–compulsive) co‐occurred significantly with depressive symptoms. Copyright © 2013 John Wiley & Sons, Ltd.